Discoidin domain receptor 1 kinase activity is required for regulating collagen IV synthesis - Borza,CM; Su,Y; Tran,TL; Yu,L; Steyns,N; Temple,KJ; Skwark,MJ; Meiler,J; Lindsley,CW; Hicks,BR; Leitinger,B; Zent,R; et al. (Matrix Biology, 2016)
Discoidin domain receptor 1 (DDR1) is a receptor tyrosine kinase that binds to and is activated by collagens. DDR1 expression increases following kidney injury and accumulating evidence suggests that it contributes to the progression of injury. To this end, deletion of DDR1 is beneficial in ameliorating kidney injury induced by angiotensin infusion, unilateral ureteral obstruction, or nephrotoxic nephritis. Most of the beneficial effects observed in the DDR1-null mice are attributed to reduced inflammatory cell infiltration to the site of injury, suggesting that DDR1 plays a pro-inflammatory effect. The goal of this study was to determine whether, in addition to its pro-inflammatory effect, DDR1 plays a deleterious effect in kidney injury by directly regulating extracellular matrix production. We show that DDR1-null mice have reduced deposition of glomerular collagens I and IV as well as decreased proteinuria following the partial renal ablation model of kidney injury. Using mesangial cells isolated from DDR1-null mice, we show that these cells produce significantly less collagen compared to DDR1-null cells reconstituted with wild type DDR1. Moreover, mutagenesis analysis revealed that mutations in the collagen binding site or in the kinase domain significantly reduce DDR1-mediated collagen production. Finally, we provide evidence that blocking DDR1 kinase activity with an ATP-competitive small molecule inhibitor reduces collagen production. In conclusion, our studies indicate that the kinase activity of DDR1 plays a key role in DDR1-induced collagen synthesis and suggest that blocking collagen-mediated DDR1 activation may be beneficial in fibrotic diseases.